A genomic and phenotypic investigation of pigeon-adaptive Salmonella. - Zining Wang; Zenghai Jiang; Qianzhe Cao; Chenghao Jia; Haiyang Zhou; Chenghu Huang; Linlin Huang; Yingying Huang; Yan Li; Min Yue (PLoS Pathogens)
Salmonella, a significant threat to public safety, inflicts substantial economic losses on the poultry industry. The unique "parental feeding" breeding model of pigeon farms, against the "all-in & all-out" biosecurity strategy, makes them susceptible to Salmonella infections and subsequent outbreaks of pigeon paratyphoid. This study initially studied three pigeon paratyphoid outbreak incidents in Henan, China, in which 53 strains of pigeon-origin Salmonella Typhimurium (STM) were identified. Whole-genome sequencing (WGS) and antimicrobial-resistant profile analysis revealed that the three outbreaks were caused by distinct STM clones (ST128-DT2, ST19-DT99). Global phylogenetic analysis suggested that the United States is a possible origin, indicating a risk of intercontinental transmission via pigeon eggs. Further bacterial virulence and invasion assays, including in vitro and in vivo assays, revealed that pigeon-host-adaptive STM, compared to broad-host-range STM, carried fewer resistance genes, exhibited higher invasion indices and pseudogene levels, displayed a non-rdar (red dry and rough) phenotype, and had strong biofilm formation capability. Additionally, they showed reduced virulence and invasiveness in mice but a pigeon-adaptive feature in cogent models. The collective results support the host adaptation for pigeons among DT2 and DT99 phage-type isolates.